1979
DOI: 10.1177/016235327900200403
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of 1,200 Educators toward the Education of the Gifted and Talented: Implications for Teacher Preparation

Abstract: The purpose of this study was to provide recommendations for teacher preparation in gifted education to directors of inservice and university training programs. Recommendations were based on the responses of 1,220 kindergarten through 12th educators to a modified Likert attitude scale regarding gifted identification, programming, behavioral characteristics, and teacher recommendations for gifted programming and teacher preparation. Also investigated were the relationships between five teacher characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the case of gifted children, their genetic predispositions might include shaping their educational environments to favor their precocious learning needs (Geake, 1997b). Here, the results add to those previously that demonstrate the efficacy of CPD environments for improving teachers' attitudes toward their gifted charges (Buttery, 1978;Copenhaver & McIntyre, 1992;Gross, 1994Gross, , 1997Rubenzer & Twaite, 1981).…”
Section: Importance Of Professional Educationsupporting
confidence: 83%
“…In the case of gifted children, their genetic predispositions might include shaping their educational environments to favor their precocious learning needs (Geake, 1997b). Here, the results add to those previously that demonstrate the efficacy of CPD environments for improving teachers' attitudes toward their gifted charges (Buttery, 1978;Copenhaver & McIntyre, 1992;Gross, 1994Gross, , 1997Rubenzer & Twaite, 1981).…”
Section: Importance Of Professional Educationsupporting
confidence: 83%
“…In addition, teachers' level of experience with giftedness seems to be related to their nomination decisions: According to Gear (1978), teachers who received training in giftedness were more effective than teachers without training in giftedness (i.e., from their classes, trained teachers identified more students as gifted who were also identified as gifted by an intelligence test), but the two groups were similarly efficient (i.e., from the students who were identified as gifted by teachers with or without training, the percentage of students who were also identified as gifted by an intelligence test was equal). Rubenzer and Twaite (1979) reported that teachers with training in the area of giftedness identified more students as gifted than teachers without training. Likewise, Bianco and Leech (2010) used vignettes to describe potentially gifted students who either had or did not have a disability.…”
Section: Teachers' Nominations Of Gifted Studentsmentioning
confidence: 99%
“…In a study of more than 1,000 public school teachers, Rubenzer and Twaite (1979) found several teacher characteristics that resulted in higher identification rates of gifted students. Teachers with 6 or more years of teaching experience were significantly more likely to identify a gifted student in their classroom than those with fewer years of teaching experience.…”
Section: The Role Of Experiencementioning
confidence: 99%